Somatic embryogenesis induction in cubiu (Solanum sessiliflorum Dunal) - Stefanello, Suzana; Scapim, Carlos Alberto; Ricken Schuelter, Adilson; Reccanello Barreto, Rafael; Manzatti da Silva, Jaqueline (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2018)
Cubiu (Solanum sessiliflorum Dunal) is a solanaceous shrub native to the Amazon region that has been attracting interest from researchers and producers of other Brazilian regions. The objective of this study in vitro was to evaluate the effect of growth regulators and explants sources on the somatic embryogenesis of S. sessiliflorum Dunal. Hypocotyl and cotyledon explants from seedlings were transferred to MS culture medium supplemented with combinations of NAA (0, 5, 10 and 20 mg L-1) and KIN (0 and 1 mg L-1). Immature zygotic embryos were cultivated in MS culture medium with different concentrations of NAA (0, 2.5, 5 and 10 mg L-1) and KIN (0 and 1 mg L-1) or 2,4-D (0, 2.5, 5 and 10 mg L-1) and KIN (0 and 0.1 mg L-1). All the cotyledon and hypocotyl explants developed calluses after 30 days in the culture medium with NAA. These responses were independent of supplementing the culture medium with KIN. Embryo-like structures at several stages of development were found on the cotyledons of immature zygotic embryos growing in the MS medium supplemented with 2,4-D at 5 and 10 mg L-1. After the subcultures, new calluses originated either from pro-embryonic clusters or cellular masses cultivated in the regulator-free medium. The isolation of these regions and their transference to the regulator-free MS medium permitted the differentiation of the pro-embryonic masses into globular and heart-shaped embryos.